As orações principais em construções completivas do português: uma contribuição para o ensino - Silva, Adriana Aparecida da [UNESP] (2015)
In this work, we present a didactic-pedagogic proposal for the treatment of main clauses in subordinate sentences (completive constructions). We investigated the treatment given to main clauses in textbooks, starting from the premise that there is a deficiency in addressing these sentences, since textbooks are focused only on subordinate clauses (concerning the syntactic function they fulfill in relation to the main clause).This research was motivated by problems related to grammar teaching in the classroom. To develop our analysis, we organized a corpus made up of older textbooks (previous to PCNs) and other more current (after to PCNs), in order to to demonstrate that there was an improvement in the development of activities designed to study the substantive subordinate clauses, although we still find models stuck to traditional analysis. From a functionalist approach to language, based on studies of Castilho (2012) and Neves (2001), we discussed the semantic-pragmatic status of main clauses in complex sentences, proposing a more meaningful approach to syntax in the classroom